THE DOORS DAN TRAGEDI NIETZSCHENIAN - I Gde Jayakumara (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2016)
As Nietzsche criticized the modernity to its deepest notion, rationality, The Doors did their criticism through their songs, especially through the stage acts with full of drunkenness and brutality. According to Nietzsche, the contradictions of de facto life cannot be handled by relying on the rationality since it has boundaries and, anyway, the human is the life itself, thereby, he must create a selfhood (the self). He should be inside the life. Inevitably, The Doors music group was considered the most brutal band in the history of rock music. However, within the framework of the Nietzschean tragedy, The Doors may be baptized in the name of god Dionysius – the god of drunkenness.